Lean six sigma and TPM for the improvement of equipment maintenance process in a service sector company: a case study - Barriga Florez, Ana Laura (2024)
Currently, competitiveness within the service industry has reached outstanding levels. In the pursuit of increasing the quality and efficiency of services, the ap-proaches of continuous improvement acquire undeniable relevance. This research aimed to implement, analyze, and assess the effects of Lean Six Sigma (LSS) methodology within the service industry for process optimization through Total Productive Maintenance (TPM). The presented case study is a workshop for equipment maintenance where, through the DMAIC methodological design, Lean Six Sigma and TPM methodologies were implemented to increase process effi-ciency. The results show an efficiency increase of over 10%, reducing equipment DPMO by 53% and decreasing the total process time by 2 hours. The value of the proposed model lies in its adaptability to companies providing technological equipment services in the regional context, as well as its contribution to recent studies on the application of TPM and LSS in the service sector.